A Floor Over A Floor!

Calculus Level 5

n = 1 n n 4 7 \large \displaystyle \sum_{n=1}^{\infty} \frac{\lfloor \sqrt{n} \rfloor }{\lfloor \sqrt[4]{n} \rfloor ^7 }

The above sum can be expressed as :

a ζ ( α ) + b ζ ( β ) + c d ζ ( γ ) + e ζ ( δ ) + f g ζ ( ϵ ) \displaystyle a\zeta (\alpha) + b\zeta (\beta) + \frac{c}{d} \zeta (\gamma) + e \zeta (\delta) +\frac{f}{g} \zeta (\epsilon)

Where a , b , c , d , e , f , g , α , β , γ , δ , a,b,c,d,e,f,g,\alpha,\beta,\gamma,\delta, and ϵ \epsilon are positive integers with c c and d d being coprime, f f and g g are also coprime.

Find : a + b + c + d + e + f + g + α + β + γ + δ + ϵ a+b+c+d+e+f+g+\alpha +\beta +\gamma +\delta +\epsilon .

Details and Assumptions :

x \bullet \lfloor x \rfloor Denotes the Floor Function.

ζ ( x ) \bullet \zeta ( x) is the Riemann Zeta Function.

Try my other calculus challenges here


The answer is 86.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Hasan Kassim
Jul 8, 2015

Note that for a certain integer k k :

x = k if x [ k , k + 1 ) \displaystyle \lfloor x \rfloor = k \; \;\;\; \text{if} \;\; x\in [k,k+1)

Let

k n 4 < k + 1 \displaystyle k\leq \sqrt[4]{n} < k+1

Where k k is an integer ranging between 1 and \infty .

So for a certain k k :

k 4 n < ( k + 1 ) 4 \displaystyle k^4 \leq n < (k+1)^4

So our sum can be written as:

S = k = 1 n = k 4 ( k + 1 ) 4 1 n k 7 \displaystyle S = \sum_{k=1}^{\infty} \sum_{n=k^4}^{(k+1)^4-1} \frac{\lfloor \sqrt{n} \rfloor }{k^7}

Now focus on the sum:

S = n = k 4 ( k + 1 ) 4 1 n \displaystyle S' = \sum_{n=k^4}^{(k+1)^4-1} \lfloor \sqrt{n} \rfloor

Let

m n < m + 1 \displaystyle m\leq \sqrt{n} < m+1

Where m m is an integer ranging between k 2 k^2 and ( k + 1 ) 2 1 (k+1)^2-1 . (This to maintain the interval of n n in S S' .)

So for a certain m m :

m 2 n < ( m + 1 ) 2 \displaystyle m^2 \leq n < (m+1)^2

So S S' can be written as:

m = k 2 ( k + 1 ) 2 1 n = m 2 ( m + 1 ) 2 1 m \displaystyle \sum_{m=k^2}^{(k+1)^2 -1 } \sum_{n=m^2}^{(m+1)^2-1 } m

= m = k 2 ( k + 1 ) 2 1 ( m ) ( ( m + 1 ) 2 1 m 2 + 1 ) \displaystyle = \sum_{m=k^2}^{(k+1)^2 -1 } (m)((m+1)^2-1 - m^2 +1)

This Sum can be easily manipulated (maybe tedious) using the formulas :

n = 1 k n = k ( k + 1 ) 2 \displaystyle \sum_{n=1}^{k} n = \frac{k(k+1)}{2}

n = 1 k n 2 = k ( k + 1 ) ( 2 k + 1 ) 6 \displaystyle \sum_{n=1}^{k} n^2 = \frac{k(k+1)(2k+1)}{6}

To get at last the value of S S' :

S = 5 3 k + 7 k 2 + 34 3 k 3 + 10 k 4 + 4 k 5 \displaystyle S' = \frac{5}{3} k + 7k^2 + \frac{34}{3} k^3 + 10k^4 + 4k^5

Now substitute this in S S and Use the fact:

ζ ( n ) = k = 1 1 k n \displaystyle \zeta(n) = \sum_{k=1}^{\infty} \frac{1}{k^n}

To get:

S = 4 ζ ( 2 ) + 10 ζ ( 3 ) + 34 3 ζ ( 4 ) + 7 ζ ( 5 ) + 5 3 ζ ( 6 ) \displaystyle \boxed{S = 4\zeta (2) + 10\zeta (3) + \frac{34}{3} \zeta (4) + 7 \zeta (5) +\frac{5}{3} \zeta (6) }

That looks exactly the same as mine except that I wouldn't have used the center alignment for every math in my solution. That doesn't look good to me(well, that's just a feedback, an opinion).

Kartik Sharma - 5 years, 11 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...